Life-span prediction of abandoned reinforced concrete residential buildings. (1st June 2016) - Ismail, Mohammad; Yew, Chan Kee; Muhammad, Bala
Highlights: Degradations on RC caused by environmental factors were investigated. Abandoned residential projects suffer from efflorescence, cracks and corrosion. Reduction in the tensile strength of reinforcement was observed. Life-span of concrete could be predicted using performance-depreciation graph. Abstract: The paper presents research findings on the deteriorating conditions of abandoned residential projects due to environmental factors of degradations. Sampling was made from two hundred and sixty-one abandoned housing projects. Structural degradations associated with the uncompleted buildings were studied. In a similar manner, a small-scale reinforced concrete structure was erected in an open and critically monitored for defects caused by environmental factors of degradations. The selected uncompleted buildings were assessed for surface salt deposits, crack formations and reinforcement corrosion. However, the small-scale structure was evaluated for performance degradations through destructive and non-destructive strength tests, steel tensile strength test and corrosion test. Results show that there is an alarming decrease in structural integrity and durability functions in abandoned reinforced concrete buildings with time. Eventually, performance-depreciation versus age graph was developed for assessing life-span limit beyond which unacceptable mechanical properties are eminent. Based on the surrounding exposure conditions, an abandoned reinforced concrete building could fail to perform acceptable designed strength functions within a period of twelve (12) years.